Breeding stages affect egg recognition in azure-winged magpies (Cyanopica cyanus) - Jianping Liu; Fudong Zhou; Hanlin Yan; Wei Liang (Animal Cognition)
Abstract Egg rejection often involves a cognitive process of recognizing foreign eggs, which can vary not only between species or among different individuals of the same species, but also within the same individual during different breeding stages, leading to markedly different responses to parasitic eggs. We conducted a comparative study in Wuhan, Hubei, and Fusong, Jilin, China, on the recognition and rejection behavior of azure-winged magpies (Cyanopica cyanus) at different breeding stages (pre-egg-laying, one-host-egg, multi-host-egg and early incubation stages). In the Fusong population, there was a significant difference in the rejection rate of model eggs by azure-winged magpies at different stages of the egg-laying period. During the one-host-egg stage, the rejection rate (63.6%) was significantly lower than that during the pre-egg-laying stage (85.7%) and the multi-host-egg stage (100%). The population of azure-winged magpies in Wuhan exhibited a 100% rejection rate towards model eggs during the pre-egg-laying stage. Furthermore, during the incubation stage, azure-winged magpies were able to accurately recognize and reject foreign eggs even when those were in majority. This indicates that azure-winged magpies employ a template-based recognition mechanism rather than relying on discordance mechanism for recognition after the onset of incubation. This study suggests that while azure-winged magpies can truly recognize their own eggs, different breeding stages still influence their rejection response towards parasitic eggs, especially during the pre-egg-laying and egg laying stages.